Effect of Different Levels of a Commercially Available Acidifier on Growth Performance, Meat Quality and Escherichia coli Count in the Ileum of Broiler Chicken - Gunawardana, K.G.U.I.P.; Weerasinghe, W.M.S.S.; Priyadarshana, S.P.M.; Sethukali, A.; De Silva, P.G.J.C.; Nambapana, N.M.N.; Jayasena, D.K.D.D. (Uva Wellassa University, Sri Lanka., 2018)
The study reported herein was conducted to investigate the effect of different levels of an acidifier on performance, meat quality, E. coli count in the ileum and the organ weights of broilers. A total of 120-day-old male broiler chicks were randomly assigned into four treatments. Each treatment comprised three replicates of 10 birds each. Broiler chicks were randomly assigned into three acidifier levels (0.5, 1.0 and 1.5 ml/3L) as T1, T2, T3 treatments, respectively. The control group (To) treated with normal water only. Broilers were fed with a basal diet for 42 days in a completely randomized design. The highest (p < 0.05) daily body weight gain (67 g) and the lowest (p<0.05) feed conversion ratio (FCR) (1.48) were recorded from T2 treatment. The lowest (p < 0.05) E. coli count (7.314 log cfu g1) in the ileal digesta content was recorded from T3 treatment. The lowest (p < 0.05) cook loss (31%) was recorded from the control group. The lowest (p < 0.05) lightness (65.7) and the highest (p<0.05) redness (10.08) of broiler breast meat were recorded from T2 treatment. The highest (p < 0.05) relative weight of the proventriculus (0.39%) was recorded from To treatment. The highest (p < 0.05) relative weights of the duodenum (0.4%) and the caeca (0.3%) were recorded from To treatment and the lowest relative weights of the duodenum (0.22%) and the ceca (0.19%) were recoded from T2 treatment. The highest (p < 0.05) relative weights of the heart (0.67%) and the pancreas (0.27%) were recorded from To treatment and the lowest relative weights of the heart (0.42%) and the pancreas (0.09%) were observed from T2 treatment. In conclusion, supplementation of an acidifier in 1ml/3L concentration has better effects on performance, E. coli count of the ileum and organ weights of broiler chicken.
Keywords: Acidifier; Feed conversion ratio; Relative weight; Weight gain